Proceedings of the 2011 iConference 2011
DOI: 10.1145/1940761.1940768
|View full text |Cite
|
Sign up to set email alerts
|

Information source and its relationship with the context of information seeking behavior

Abstract: Past studies on a person's choice of information sources have shown mixed results because of a lack of understanding of the 'context' surrounding information seeking that impacts a person's choice of an information source. The Contextual Identity Framework combines three conflicting views of context to try and define its boundaries in information behavior. However, it is not clear in which of these three views of context would 'information source' fit. Would it be part of the shared context or contextual stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It could be those with first-hand experience, such as engineers on the same project or senior students who took the course previously. It could also result from successfully receiving information from this individual previously (Allard, Levine, and Tenopir 2009;Du Preez 2007;Agarwal 2011).…”
Section: Seeking Information For the Fastest Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be those with first-hand experience, such as engineers on the same project or senior students who took the course previously. It could also result from successfully receiving information from this individual previously (Allard, Levine, and Tenopir 2009;Du Preez 2007;Agarwal 2011).…”
Section: Seeking Information For the Fastest Resultsmentioning
confidence: 99%
“…A study by Allard et al (2009) found that some engineers were using the Internet for a first stop to find information; however, context cannot be ignored when assessing information seeking behavior (Agarwal 2011). Many of the engineers in the study were software developers, where a noted use of the Internet was looking for solutions to specific code problems.…”
Section: Seeking Information For the Fastest Resultsmentioning
confidence: 99%
“…A challenging aspect of the fake news problem is the massive information overload associated with the widespread use of social media platforms as a source of daily information. As of 2020, the information behavior of people include drawing information from a variety of synchronous and asynchronous sources and channels (Agarwal et al , 2011; Agarwal, 2011), e.g. from friends and contacts reached face-to-face, or via phone, audio/video calls, email, or messaging apps; online information; and social media like Facebook, Twitter, Instagram and LinkedIn (Agarwal, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kingrey (2005) described that information seeking involves divergent things in divergent contexts for searching, retrieving, comprehension and practice of meaningful material. Agarwal (2011) stated that traditional sources i.e. books, magazines, persons and the contemporary sources, such as e-libraries and online search engines are available for information.…”
Section: Introductionmentioning
confidence: 99%